Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(ax+2x+ay+2y+4\)
\(\Leftrightarrow x\left(a+2\right)+y\left(a+2\right)+4\)
\(=\left(x+y\right)\left(a+2\right)+4\)
\(=a^2-4+4=a^2\)
a) Thiếu ĐK: \(a+b+c=0\)
Giải:
Ta có:
\(a^3+a^2c-abc+b^2c+b^3\)
\(=a^3+a^2c+a^2b-a^2b-abc+b^2c+b^3+b^2a-b^2a\)
\(=a^2\left(a+b+c\right)-a^2b-abc+b^2\left(a+b+c\right)-b^2a\)
\(=-a^2b-abc-b^2a\)
\(=-ab\left(a+b+c\right)\)
Mà \(a+b+c=0\) nên:
\(=-ab.0\)
\(=0\)
Vậy \(a^3+a^2c-abc+b^2c+b^3=0\) (Đpcm)
Bài 1:
a) \(f\left(x\right)=2x\left(x^2-3\right)-4\left(1-2x\right)+x^2\left(x-1\right)+\left(5x+3\right)\)
\(=2x^3-6x-4+8x+x^3-x^2+5x+3\)
\(=x^3-x^2+7x-1\)
\(g\left(x\right)=-3\left(1-x^2\right)-2\left(x^2-2x+1\right)\)
\(=-3+3x^2-2x^2+4x-2\)
\(=x^2+4x-5\)
b) \(h\left(x\right)=f\left(x\right)-g\left(x\right)\)
\(=x^3-x^2+7x-1-x^2-4x+5\)
\(=x^3-2x^2+3x-4\)
\(ac+b^2-2x^4y^4=x^3y.xy^3+\left(x^2y^2\right)^2-2x^4y^4\)
\(=x^4y^4+x^4y^4-2x^4y^2\)
\(=0\)
Vậy... (đpcm)
ax+2x+ay+2y+4
=a(x+y)+2(x+y)+4
=(a+2)(x+y)+4
=(a+2)(a-2)+4
=a^2-4+4
=a^2
Với a - 2 = x + y ta có :
ax + 2x + ay + 2y + 4
= ( ax + ay ) + ( 2x + 2y ) + 4
= a ( x + y ) + 2 ( x + y ) + 4
= ( a + 2 ) ( x + y ) + 4
= ( a + 2 ) ( a - 2 ) + 4
= a2 - 4 + 4 = a2 (đpcm)